1988
DOI: 10.1210/jcem-66-4-659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Basal and Adrenocorticotropin- Stimulated Plasma 21-Deoxycortisol and 17-Hydroxyprogesterone Values as Biological Markers of Late-Onset Adrenal Hyperplasia

Abstract: Plasma 21-deoxycortisol (21-DOF) and 17-hydroxyprogesterone (17-OHP) concentrations were assayed before (basal) and 1 h after ACTH stimulation in 4 groups of normal subjects (35 follicular phase women, 22 luteal phase women, 33 adult men, and 15 prepubertal children) and in a group of 31 patients with the late-onset form of congenital adrenal hyperplasia (LOCAH) due to 21-hydroxylase deficiency as well as in 31 LOCAH) heterozygotes. The mean basal plasma 21-DOF concentrations in each of the 4 groups of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 27 publications
4
32
0
4
Order By: Relevance
“…Impaired 21-hydroxylase activity was assumed when the poststimulation 17-OHP level exceeded 15 nmol/l (22). Poststimulated 21-DF levels over 2.2 nmol/l were taken as indicative of 21-hydroxylase impairment (20,21). A post-stimulative S/F ratio above 0.12 was taken as indicative of an altered 11b-hydroxylase activity; this cut-off value was determined from previously published studies (12,(23)(24)(25).…”
Section: Endocrine Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired 21-hydroxylase activity was assumed when the poststimulation 17-OHP level exceeded 15 nmol/l (22). Poststimulated 21-DF levels over 2.2 nmol/l were taken as indicative of 21-hydroxylase impairment (20,21). A post-stimulative S/F ratio above 0.12 was taken as indicative of an altered 11b-hydroxylase activity; this cut-off value was determined from previously published studies (12,(23)(24)(25).…”
Section: Endocrine Assessmentmentioning
confidence: 99%
“…Conversely, only one subject displayed a peak 21-DF value in the normal range whereas ten had levels above 2.2 nmol/l, a cut off that has been shown to separate normal subjects from heterozygous or homozygous carriers of 21-hydroxylase deficiency (20,21). Although peak 17-OHP and peak 21-DF provide comparable results, we suggest that for individual patients peak 21-DF determination is better given its greater specificity (20,21). This study did not identify predictive parameters indicating an impaired 21-hydroxylase activity.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…With a >10 ng/ml cut-off, Morel and Tardy (101) showed that nearly 100% of patients with genetically proven NCAH, regardless of the type of mutation, could be identified. This very accurate cut-off value is routinely used for NCAH screening in hyperandrogenic women (102,103,104,105,106). In the near future, the development of sequencing platforms should enable routine sequencing of the CYP21A2 gene.…”
Section: Screening For Non-classical Congenital Adrenal Hyperplasia (mentioning
confidence: 99%
“…Estos trastornos pueden confundirse con cierta frecuencia con el sindrome de ovario poliqufstico porque, ademas de signos clinicos de hiperandrogenismo, la ecografia ovarica revela a veces imagenes qui'sticas similares en ambas enfermedades 12 ' 13 . Solo un acucioso estudio hormonal en condiciones basales, con pruebas de estimulacion con ACTH y luego frenacion, permiten en la mayoria de los casos el diagnostico correcto 6 ' 7 ' Hl 1S . A continuacion se describe una estrategia realizada para detectar, en un grupo de pacientes con hirsutismo de etiologi'a no precisada, aquellas en que la causa puede ser de origen suprarrenal y sus resultados.…”
unclassified